Insulin requires normal expression and signaling of insulin receptor A to reverse gestational diabetes‐reduced adenosine transport in human umbilical vein endothelium. Issue 1 (28th October 2014) - Westermeier, Francisco; Salomón, Carlos; Farías, Marcelo; Arroyo, Pablo; Fuenzalida, Bárbara; Sáez, Tamara; Salsoso, Rocío; Sanhueza, Carlos; Guzmán‐Gutiérrez, Enrique; Pardo, Fabián; Leiva, Andrea; Sobrevia, Luis
Abstract : Reduced adenosine uptake via human equilibrative nucleoside transporter 1 (hENT1) in human umbilical vein endothelial cells (HUVECs) from gestational diabetes mellitus (GDM) is reversed by insulin by restoring hENT1 expression. Insulin receptors A (IR‐A) and B (IR‐B) are expressed in HUVECs, and GDM results in higher IR‐A mRNA expression vs. cells from normal pregnancies. We studied whether the reversal of GDM effects on transport by insulin depends on restoration of IR‐A expression.We specifically measured hENT1 expression [mRNA, protein abundance, SLC29A1 (for hENT1) promoter activity] and activity (adenosine transport kinetics) and the role of IR‐A/IR‐B expression and signaling [total and phosphorylated 42 and 44 kDa mitogen‐activated protein kinases (p44/42 mapk ) and Akt] in IR‐A, IR‐B, and IR‐A/B knockdown HUVECs from normal ( n = 33) or GDM ( n = 33) pregnancies. GDM increases IR‐A/IR‐B mRNA expression (1.8‐fold) and p44/ 42 mapk :Akt activity (2.7‐fold) ratios. Insulin reversed GDM‐reduced hENT1 expression and maximal transport capacity( Vmax /Km ), andGDM‐increased IR‐A/IR‐B mRNA expression and p44/42 mapk :Akt activity ratios to values in normal pregnancies. Insulin's effect was abolished in IR‐A or IR‐A/B knockdown cells. Thus, insulin requires normal IR‐A expression and p44/42 mapk /Akt signaling to restore GDM‐reduced hENT1 expression and activity in HUVECs. This could be a protective mechanism for the placental macrovascular endothelial dysfunction seen in GDM.‐Westermeier, F., Salomon, C., Farías, M., Arroyo, P., Fuenzalida, B., Sáez, T., Salsoso, R., Sanhueza, C., Guzmán‐Gutiérrez, E., Pardo, F., Leiva, A., Sobrevia, L. Insulin requires normal expression and signaling of insulin receptor A to reverse gestational diabetes‐reduced adenosine transport in human umbilical vein endothelium. FASEB J. 29, 37–49 (2015). www.fasebj.org